The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1063/1.2767273
|View full text |Cite
|
Sign up to set email alerts
|

The influence of magnetic dilution in the Zn1−xMnxGa2Se4 series with 0.5<x⩽1

Abstract: The Zn1−xMnxGa2Se4 system with 0.5<x<1, which represents a magnetic dilution of the tetragonal MnGa2Se4, retains the defective chalcopyrite structure of the parent compound. Neutron powder diffraction experiments and temperature dependent magnetic susceptibility measurements show that such dilution has a significant influence on the magnetic properties of the system. The distance between the closest magnetic atoms decreases from a to a∕2Å (where a is the lattice parameter and a≈5.6Å), making the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Room temperature parameters obtained in this work are in good agreement with [12] and [13] The dependence of a, c and σ with temperature and composition is attributed to the combined effect of thermal expansion and changes in the degree of structural order, both at the phase transition and before. For chalcopyrite materials it has been shown that anisotropic thermal expansion occurs, yielding in general an increase of the tetragonal distortion with temperature [31].…”
Section: Neutron Diffractionsupporting
confidence: 79%
See 2 more Smart Citations
“…Room temperature parameters obtained in this work are in good agreement with [12] and [13] The dependence of a, c and σ with temperature and composition is attributed to the combined effect of thermal expansion and changes in the degree of structural order, both at the phase transition and before. For chalcopyrite materials it has been shown that anisotropic thermal expansion occurs, yielding in general an increase of the tetragonal distortion with temperature [31].…”
Section: Neutron Diffractionsupporting
confidence: 79%
“…As regards the Zn 1-x Mn x Ga 2 Se 4 series, electronic band gap and magnetic properties have been shown to vary non-monotonically with composition [9][10][11], a fact that has been attributed to a varying degree of disorder along the series. This hypothesis has been verified in a structural study performed by means of time of flight (TOF) neutron diffraction at room temperature (RT) [10][11][12][13]. As reported in [10], the degree of order is closely related to the Mn occupancy of the available sites: 2d and 2c (if the space group is I-4) or 4d (if it is I- Mn partially occupies the 2d and 2c sites, resulting in 0< η <1.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…To this respect, while some authors claim that ZnGa 2 Se 4 crystallizes in the tetragonal ordered defect chalcopyrite (DC) structure with space group (SG) I-4 [see Fig. 1(a)] where cations and vacancies are completely ordered, 7,13,15,16,22 other authors report that ZnGa 2 Se 4 crystallizes in the partially disordered tetragonal defect stannite (DS) structure, also known as defect famatinite, with SG I-42 m and higher symmetry than the DC phase [8][9][10][11][12]21,26 [see Fig. 1(b)].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In particular, ZnGa 2 Se 4 has a high photosensitivity and strong luminescence, 2 can be used for phase change memories, 5 and has been proposed as a candidate for electronic device applications forming part of heterojunction diodes. 6 The properties of ZnGa 2 Se 4 have been characterized by x-ray diffraction (XRD), 7,8 neutron and electron diffraction, [9][10][11][12] extended x-ray absorption fine structure, 13 infrared (IR), 14,15 Raman spectroscopy, [15][16][17][18][19][20][21][22][23][24] and magnetic 25 measurements. To this respect, while some authors claim that ZnGa 2 Se 4 crystallizes in the tetragonal ordered defect chalcopyrite (DC) structure with space group (SG) I-4 [see Fig.…”
Section: Introductionmentioning
confidence: 99%